HUBUNGAN KELESUAN MELAMPAU (BURNOUT) DAN PRESTASI KERJA DALAM KALANGAN ANGGOTA POLIS DI IBU PEJABAT POLIS (IPD) DAERAH HILIR PERAK TELUK INTAN, PERAK - Omar, Nurul Najiha; Yusof, Faudziah (Jurnal ’Ulwan, 2023)
Work performance is greatly influenced by external and internal factor of an employee himself. Symptoms of burnout or extreme stress are a major problem for some front-line workers because they have to work with commitment for a long period of time. Therefore, the level of stress and mental health is able to affect a person’s work performance. This study was conducted to examine the relationship between burnout and work performance among police officers at police headquarters (IPD) Hilir Perak District Teluk Intan Perak. A set of questionnaires of three parts containing respondent’s demographic information, Maslach Burnout Inventory (MBI) and Work Performance questionnaire was used to collect data on 120 respondents. All data was analyzed using the Statistical Package for the Social Sciences (SPSS) software version 25. the results of the study found that there is a significant relationship between burnout and work performance among police officers [r = -.201, p